Trypanosoma cruzi strain and starvation-driven mitochondrial RNA editing and transcriptome variability - Gerasimov, Evgeny S; Ramirez-Barrios, Roger; Yurchenko, Vyacheslav; Zimmer, Sara L (RNA (New York, N.Y.), 2022)
Trypanosoma cruzi is a unicellular protistan parasitic species that is comprised of strains and isolates exhibiting high levels of genetic and metabolic variability. In the insect vector, it is known to be highly responsive to starvation, a signal for progression to a life stage in which it can infect mammalian cells. Most mRNAs encoded in its mitochondrion require the targeted insertion and deletion of uridines to become translatable transcripts. This study defined differences in uridine-insertion/deletion RNA editing among three strains and established the mechanism whereby abundances of edited (and, thus, translatable) mitochondrial gene products increase during starvation. Our approach utilized our custom T-Aligner toolkit to describe transcriptome-wide editing events and reconstruct editing products from high-throughput sequencing data. We found that the relative abundance of mitochondrial transcripts and the proportion of mRNAs that are edited varies greatly between analyzed strains, a characteristic that could potentially impact metabolic capacity. Starvation typically led to an increase in overall editing activity rather than affecting a specific step in the process. We also determined that transcripts CR3, CR4, and ND3 produce multiple open reading frames that, if translated, would generate different proteins. Finally, we quantitated the inherent flexibility of editing in T. cruzi and found it to be higher relative to that in a related trypanosomatid lineage. Over time, new editing domains or patterns could prove advantageous to the organism and become more widespread within individual transcriptomes or among strains.
Keywords: RNA Editing; messenger RNA; editace RNA; transkriptom; epimastigote; Trypanosoma cruzi; RNA, Mitochondrial; electron transport chain; protozoální proteiny; Transcriptome; RNA; RNA mitochondriální; Chagas disease; RNA, Messenger; zvířata; Mammals; Protozoan Proteins; savci; Trypanosoma brucei brucei; metabolism; RNA protozoální; RNA editing; RNA, Protozoan; Animals